Muon's Anomalous Magnetic Moment Effects on Laser Assisted Coulomb Scattering Process (Journal of Atomic and Molecular Sciences, 2013)
Laser assisted Coulomb scattering by relativistic electron and heavy electron (muon) is studied by using Salamin waves [3] in the Weak Field Approximation (WFA). Both electron and muon are described by the Dirac equation, with the anomalous magnetic moment effects fully included. The generalization of this paper to heavy electron (muon) gives interesting insights as to how the mass affects the magnitude of the differential cross sections. No significant difference in the muon's DCS with and without AMM effects was detected.